Job Satisfaction as a Mediator of The Effects of Emotional Intelligence and Digital Literacy on Employee Performance at PT Pos Indonesia KC Purworejo - Wandhani, Fatonah Isnaini; Utaminingsih, Adijati; Widhiastuti, Hardani (Universitas Muhammadiyah Pontianak, 2026)
This study examines the effects of emotional intelligence and digital literacy on employee performance, with job satisfaction as a mediating variable, at PT Pos Indonesia, Purworejo Branch. Using a quantitative approach, data were collected from 80 employees through structured questionnaires and analyzed using PLS-SEM with SmartPLS 4.0. The findings reveal that emotional intelligence positively and significantly influences both job satisfaction and employee performance. Digital literacy significantly affects job satisfaction but has no direct effect on performance. Mediation analysis confirms that job satisfaction mediates the relationships between emotional intelligence and performance, as well as between digital literacy and performance.